A simple proof of the four-colors theorem - Smoluk, Antoni (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The paper includes an inductive proof of the four-color theorem. The notions of producing maps and minimum local colorings are applied.
Didactics of Mathematics, 2016, No. 13(17), s. 35-38
Keywords: minimum local coloring; extension of local coloring; dissecting ring; simple map; production of maps